Observation-based modelling of the energetic storm particle event of 14 July 2012 - Wijsen N.; Aran A.; Scolini C.; Lario D.; Afanasiev A.; Vainio R.; Sanahuja B.; Pomoell J.; Poedts S. (EDP Sciences, 2025)
Aims. We model the energetic storm particle (ESP) event of 14 July 2012 using the energetic particle acceleration and transport model named 'PArticle Radiation Asset Directed at Interplanetary Space Exploration' (PARADISE), together with the solar wind and coronal mass ejection (CME) model named 'EUropean Heliospheric FORcasting Information Asset' (EUHFORIA). The simulation results illustrate both the capabilities and limitations of the utilised models. We show that the models capture some essential structural features of the ESP event; however, for some aspects the simulations and observations diverge. We describe and, to some extent, assess the sources of errors in the modelling chain of EUHFORIA and PARADISE and discuss how they may be mitigated in the future.
Methods. The PARADISE model computes energetic particle distributions in the heliosphere by solving the focused transport equation in a stochastic manner. This is done using a background solar wind configuration generated by the ideal magnetohydrodynamic module of EUHFORIA. The CME generating the ESP event is simulated by using the spheromak model of EUHFORIA, which approximates the CME's flux rope as a linear force-free spheroidal magnetic field. In addition, a tool was developed to trace CME-driven shock waves in the EUHFORIA simulation domain. This tool is used in PARADISE to (i) inject 50 keV protons continuously at the CME-driven shock and (ii) include a foreshock and a sheath region, in which the energetic particle parallel mean free path, lambda(parallel to), decreases towards the shock wave. The value of lambda(parallel to) at the shock wave is estimated from in situ observations of the ESP event.
Results. For energies below similar to 1 MeV, the simulation results agree well with both the upstream and downstream components of the ESP event observed by the Advanced Composition Explorer. This suggests that these low-energy protons are mainly the result of interplanetary particle acceleration. In the downstream region, the sharp drop in the energetic particle intensities is reproduced at the entry into the following magnetic cloud, illustrating the importance of a magnetised CME model.